2019
DOI: 10.1097/njh.0000000000000617
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Perspectives on the Use of the Edmonton Symptom Assessment System (Revised) in Palliative Care

Abstract: The Edmonton Symptom Assessment System (Revised) (ESAS-r) contains 9 questions pertaining to symptoms/well-being. It is a standardized patient-reported assessment instrument, but inconsistently used in palliative care. Thus, a problem exists in knowledge translation regarding routine use of the ESAS-r in palliative practice. The objective was to understand clinicians' perspectives on the use of the ESAS-r in palliative care in hospitals and at home. Qualitative focus groups (n = 14 with 46 clinicians) and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“… 51 , 70 , 72 75 Appropriate training of HCPs to handle and respond to ePROM data needs to be provided in order to facilitate integration with existing clinical workflows. 43 , 66 , 76 LeRouge et al have recently published a comprehensive toolkit to facilitate the process of implementation and integration of ePROMs with existing health systems. 77 This toolkit comprises of guidelines that focus on the various aspects of the process including ePROM integration approaches, workflow designing, leveraging of health ICT, and display of data.…”
Section: Challenges With the Use Of Epromsmentioning
confidence: 99%
See 4 more Smart Citations
“… 51 , 70 , 72 75 Appropriate training of HCPs to handle and respond to ePROM data needs to be provided in order to facilitate integration with existing clinical workflows. 43 , 66 , 76 LeRouge et al have recently published a comprehensive toolkit to facilitate the process of implementation and integration of ePROMs with existing health systems. 77 This toolkit comprises of guidelines that focus on the various aspects of the process including ePROM integration approaches, workflow designing, leveraging of health ICT, and display of data.…”
Section: Challenges With the Use Of Epromsmentioning
confidence: 99%
“…11,[66][67][68] Concerns about workload; individual values, beliefs and priorities; lack of specific competence dealing with issues relating to emotional problems; PROM standardisation and quantification were noted as some of the determinants of HCP attitudes. 11,[66][67][68] A recent meta-synthesis by Easpiag et al showed an encouraging overall positive polarity of opinions among HCPs. 69 An awareness of the tensions and challenges experienced by HCPs with ePROMs and their engagement and involvement in ePROM system development, implementation and integration is essential to overcome these barriers.…”
Section: Cost and Cost-effectivenessmentioning
confidence: 99%
See 3 more Smart Citations